Development care for children with special health needs in home care at Paraná - Brazil - Vanessa Rossetto; Beatriz Rosana Gonçalves de Oliveira Toso; Rosa Maria Rodrigues; Cláudia Silveira Viera; Eliane Tatsch Neves (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objective: To describe the development of care for children with special health needs in Paraná services of homecare. Method: Quantitative, descriptive, exploratory, and multiple case study was applied. Data were collected by telephone and e-mail, with professionals from the eight services of homecare of Parana, from October 2016 to January 2017. The data was treated with descriptive statistics analysis. Results: Among 35 children in homecare, 25.7% had cerebral palsy, 60% had a tracheostomy. The care provided by the services includes a management of tubes, administration of medication, changing dressings, caregiver guidance for tracheostomy suctioning and a management of diet. Conclusions and implications for practice: Services weaknesses were mainly related to low utilization of the singular therapeutic project and the counter-reference to primary care. The flow of successful practices are developed in the municipality of an isolated manner. Showing positive experiences promotes reflection and improvement of the work process of caring for children with special health needs in homecare.